Graphite as a Long‐Life Ca2+‐Intercalation Anode and its Implementation for Rocking‐Chair Type Calcium‐Ion Batteries. Issue 24 (16th October 2019) - Richard Prabakar, S. J.; Ikhe, Amol Bhairuba; Park, Woon Bae; Chung, Kee‐Choo; Park, Hwangseo; Kim, Ki‐Jeong; Ahn, Docheon; Kwak, Joon Seop; Sohn, Kee‐Sun; Pyo, Myoungho
Abstract: Herein, graphite is proposed as a reliable Ca 2+ ‐intercalation anode in tetraglyme (G4 ). When charged (reduced), graphite accommodates solvated Ca 2+ ‐ions (Ca‐G4 ) and delivers a reversible capacity of 62 mAh g −1 that signifies the formation of a ternary intercalation compound, Ca‐G4 ·C72 . Mass/volume changes during Ca‐G4 intercalation and the evolution of in operando X‐ray diffraction studies both suggest that Ca‐G4 intercalation results in the formation of an intermediate phase between stage‐III and stage‐II with a gallery height of 11.41 Å. Density functional theory calculations also reveal that the most stable conformation of Ca‐G4 has a planar structure with Ca 2+ surrounded by G4, which eventually forms a double stack that aligns with graphene layers after intercalation. Despite large dimensional changes during charge/discharge (C/D), both rate performance and cyclic stability are excellent. Graphite retains a substantial capacity at high C/D rates (e.g., 47 mAh g −1 at 1.0 A g −1 s vs 62 mAh g −1 at 0.05 A g −1 ) and shows no capacity decay during as many as 2000 C/D cycles. As the first Ca 2+ ‐shuttling calcium‐ion batteries with a graphite anode, a full‐cell is constructed by coupling with an organic cathode and its electrochemical performance is presented. Abstract : Graphite can intercalate/deintercalate Ca 2+ ions with excellent cyclability and rate capability. Calcium ion batteries, which consist of a graphite anode and a perylene‐3, 4, 9, 10‐tetracarboxylic dianhydride cathode in Ca(TFSI)2 /G4, can operate in a rocking‐chair mode and deliver a reversible capacity of ≈80 mAh g −1 with good stability.